Penerapan Model Pembelajaran Example Non Example pada Mata Pelajaran Matematika Siswa Kelas III di SD Negeri S Kertosari - Melica Rizqi Duwi Septiana; Aswarliansyah Aswarliansyah; Candres Abadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine whether the application of the example non example learning model can significantly improve the mathematics learning outcomes of third grade students of Kertosari State Elementary School. This type of research uses experimental methods, with a one-group pretest-posttest design. The place and time of the research was conducted at SD Negeri Kertosari, Musi Rawas Regency with the research time in the even semester. The population of this study amounted to 13 third grade students of SD Negeri S Kertosari, the research sample used saturated sampling technique. Data collection techniques Pre-Test and Post-Test with multiple choice questions as many as 15 items. From the results of data analysis using the Z-test with a significant level of ɑ = 0.05, it was found that Zcount ˃ Ztabel (4.71 ˃ 1.64), so it can be concluded that there are learning outcomes in mathematics of third grade students of Kertosari State Elementary School by applying the example non example learning model.